2011
DOI: 10.1038/clpt.2011.56
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Polymorphic OCT1: Another Piece in the Puzzle of the Variable Pharmacokinetics and Pharmacodynamics of the Opioidergic Drug Tramadol

Abstract: We investigated whether tramadol or its active metabolite, O-desmethyltramadol, are substrates of the organic cation transporter OCT1 and whether polymorphisms in OCT1 affect tramadol and O-desmethyltramadol pharmacokinetics. Tramadol showed high permeability through parallel artificial membrane permeability assays (PAMPAs). Tramadol uptake in HEK293 cells did not change after OCT1 overexpression, and the concentrations of tramadol in the plasma of healthy volunteers were independent of their OCT1 genotypes. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
141
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(149 citation statements)
references
References 36 publications
5
141
1
2
Order By: Relevance
“…The heterozygotes have only one functional OCT1 allele and constitute about 40% of Caucasian population [19]. In case of loss of OCT1 function, there is reduced uptake of drugs in liver as also reported for tramadol and metformin [23,24]. Our findings (e.g., association between rs72552763 GAT deletion and high incidence of RD) are similar and to supportive of previously published associations between loss of function OCT1 and morphine and other drug effects.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The heterozygotes have only one functional OCT1 allele and constitute about 40% of Caucasian population [19]. In case of loss of OCT1 function, there is reduced uptake of drugs in liver as also reported for tramadol and metformin [23,24]. Our findings (e.g., association between rs72552763 GAT deletion and high incidence of RD) are similar and to supportive of previously published associations between loss of function OCT1 and morphine and other drug effects.…”
Section: Discussionsupporting
confidence: 80%
“…Higher plasma morphine level will lead to greater incidences of morphine-induced PONV and RD. This SNP was reported to be associated with reduced metformin transport [26], lower tough concentration of metformin in diabetic patient [27], increased C max and reduced vomiting episodes following tropisetron and ondansetron administration [28], increased tramadol plasma level and increased miosis response in pain treatment [24]. We found that another SNP rs72552763 was also found to be associated with RD (p = 0.007).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…It is responsible for the uptake of positively charged compounds at physiological pH, such as morphine and the active metabolite of tramadol, O-desmethyltramadol (41 ). The role of SLC22A1 lossof-function polymorphisms (*2, *3, *4,*5, *6) on tramadol PK and PD was emphasized by the finding of increased O-desmethyltramadol plasma concentrations and prolonged contraction of the eye pupils (PD marker for opioid effect) in healthy volunteers (42 ). Another study in 205 adult postoperative patients on patientcontrolled analgesia found that those with 2 inactive SLC22A1 alleles had higher O-desmethyltramadol area under the concentration curve (AUC) and lower tramadol consumption during the first 24 h after surgery (43 ).…”
Section: Slc22a1mentioning
confidence: 99%
“…Genetic variants of OCT1 with reduced function have been associated with decreased response to metformin 4 as well as high systemic plasma levels of morphine and the active metabolite of the opioidergic drug tramadol. 5 Furthermore, administration of the calcium channel blocker verapamil (a potent inhibitor of OCT1) has been shown to reduce response to metformin, presumably through reducing hepatic drug levels. 6 In recognition of its critical role in drug disposition and response, OCT1 was included in a group of transporters of clinical importance by the International Transporter Consortium.…”
Section: ■ Introductionmentioning
confidence: 99%